Dynamics of blood microsatellite instability (bMSI) burden predicts outcome of a patient treated with immune checkpoint inhibitors: a case report of hyperprogressive disease - Daria Kravchuk; Alexandra Lebedeva; Alexandra Lebedeva; Olesya Kuznetsova; Olesya Kuznetsova; Alexandra Kavun; Anastasiia Taraskina; Ekaterina Belova; Ekaterina Belova; Ekaterina Belova; Tatiana Grigoreva; Tatiana Grigoreva; et al. (Frontiers in Immunology)
Microsatellite instability (MSI) is a widely studied molecular signature, which is associated with long-term benefit in patients treated with immune checkpoint inhibitor therapy. This approach has been proven to be effective in the treatment of patients with MSI-positive colorectal cancer (CRC). Analysis of serial liquid biopsy samples allows to detect changes in the tumor in response to therapy. Typically, somatic mutations are used for tracing the dynamics of the tumor, and the assessment of DNA signatures such as MSI is not currently used for these purposes. Here, we describe a case of a MSI-positive CRC, who received nivolumab monotherapy. Sequential sampling of the patient’s plasma demonstrated an increase in MSI burden (bMSI), which was found to correlate with the increase of driver mutation burden one month after starting nivolumab, and hyperprogressive disease. Thus, analysis of bMSI in liquid biopsy via NGS may be a promising method for timely assessment of the treatment effectiveness received by patients with MSI-positive CRC.